Electric Vehicle Deployment and Sustainable Corporate Practices: Evaluating the Mediating Effect of Climate Change Awareness - karma, kadek fajar andika (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The adoption of electric vehicles (EVs) and the management of climate change risks are critical considerations for enhancing corporate sustainability. This study delves into the intricate relationship between EV usage, climate change risk, and corporate sustainability within the context of Micro, Small, and Medium Enterprises (MSMEs) in Bali Province. Through the formulation of hypotheses, this research aims to scrutinize the impact of EVs on corporate sustainability and assess the mediating role of climate change risk. Data were meticulously gathered from a sample of 180 MSMEs, providing insights into their sustainability practices and perceptions. The findings reveal a noteworthy positive association between EV usage and corporate sustainability, signifying the potential of EV adoption as a catalyst for sustainable business practices. Conversely, climate change risk emerged as a significant detractor, exerting a negative influence on corporate sustainability, both directly and indirectly through its interaction with EVs. These results underscore the pivotal role of EV integration in corporate sustainability strategies, while also emphasizing the imperative for proactive measures to mitigate climate change risks. However, the complexity of these relationships suggests the need for further research endeavors to unravel the underlying mechanisms and nuances. By advancing our understanding of these dynamics, future research can offer valuable insights to inform strategic decision-making and policy development aimed at fostering sustainable business practices amidst the challenges of climate change.